VARIED SCHEMES OF TREATMENT OF CHRONIC DISEASES OF ENT-ORGANS WITH BACTERIAL LYSATES IN CHILDREN - S.V. Ryazantsev; I.A. Tikhomirova ("Paediatrician" Publishers LLC, 2009)
This article describes a problem of treatment of chronic diseases of ENT-organs, frequently developing on the basis of insufficient reactions of immunity. Also the problems of resistance of widely prevalent bacterial cultures to antibiotics, and administration of medications with not evident effectiveness are marked. Authors present a proper experience of treatment of pharyngeal tonsil with bacterial lysates mixture (IRS 19).Key words: children, ENT-organs pathology, treatment, bacterial lysates mixture.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(1):125-129)